秘密保持命令之回顧與展望 - 劉怡君; 杜佩珊; 陳俐雯; Yi-Chun Liu; Pei-Shan Tu; Li-Wen Chen (交通大學科技法律學院（原名稱：交通大學科技法律研究所）, 2020)
立法院因應國內偵查實務所需，提出由檢察官為核發機關之偵查保密令制度，作為偵查程序中衡平發現真實與營業秘密保護之手段。偵查保密令係我國因應實務所需而創建之制度，欠缺國外立法例及實務操作前例，將來偵查保密令制度之建置與執法操作，應有研議因應必要。因偵查保密令制度係發想於審理中秘密保持命令制度，本文將回顧國內及國外有關秘密保持命令制度之研究文獻與實務見解，對國內審判實務操作秘密保持命令制度之法院實務審理狀況相關議題，與實務工作者進行深度訪談，及就秘密保持命令裁定進行量化研究，分析國內與國外審判實務情況異同，提出實證研究結果及相關分析意見，並提出本文認為我國偵查保密令制度建立意義，及實務操作借鏡秘密保持命令研究成果時應注意之點，期望讓從事實務工作者能更深入瞭解我國秘密保持命令實務狀況，讓國內偵查保密令及秘密保持命令制度均能穩健成熟發展，發揮制度應有之訴訟程序中兼顧保護營業秘密及程序權利的目的。

The Legislative Yuan of Taiwan enacted “the Investigation Confidentiality Protective Order” (hereinafter referred to as “the Order”) which granted the prosecutor to issue during criminal investigation, as the method of balancing substantive justice and protection of trade secrets. It is not applied the criminal discovery rule in Taiwan, taking opportunity to legally explore the trade secret of the rivals during a criminal investigation. The Order is constituted in response to the demands of domestic investigating practices in Taiwan. Since it lacks foreign legislation and practical precedents, it is necessary to discuss how to legislate and enforce the system of the Order. Since the Order is derived from “the Confidentiality Preservation Order ,” this article reviewed domestic and foreign literatures and practical opinions of the Confidentiality Preservation Order, also conducted in-depth interview with practitioners about the issues of the enforcement of Confidentiality Preservation Order in trials, and made quantitative research of the ruling of Confidentiality Preservation Order. The text analyzed implementation of the Confidentiality Preservation Order between the domestic and foreign trial practices, and presented the results of the empirical research and the related observations. Also, this article claimed the significance of the legislation of the Order, and reminded the precautions in the application of the Order by observing the implementation of the Confidentiality Preservation Order. The study expected to make practitioners have a deeper and broader understanding of the practical implication of the Confidentiality Preservation Order, and develop the system of the Order and the Confidentiality Preservation Order without hesitation. The purpose of legislation is to balance trade secrets protection and procedural due process.
The Confidentiality Preservation Order in Taiwan －Review and Response
Keywords: 營業秘密; 秘密保持命令; 審酌要素; 證據開示; Trade Secret; Protective Order / Confidentiality Preservation Order / Investigation Confidentiality Protective Order; Examination Factor; Discovery